The Moderating Role of Liquidity on Financial Leverage and Profitability of Banks in Ghana - Ibrahim, Abdul Rafiu; Nagriwum, Timothy Masuni; Wiredu, Richard; Adam, Dauda (International Journal of Finance, 2024)
Purpose: In the banking industry, profitability has always been a key metric for determining or analyzing profitability. Changes in bank profitability could have an impact on economic advancement since earnings influence company investment decisions. As a result, significant profitability is necessary for a bank's long-term survival and growth. The paper examined the role of liquidity on the nexus between financial leverage and profitability of banks from the perspective of Ghana. Methodology: Based on convenience sampling techniques and the availability of reliable data, the study covered six (2018-2023) financial years of the twenty (20) banks. The study employed quantitative research with descriptive and exploratory research design. SPSS (v23) and Microsoft Excel were used in analyzing the secondary data collected from the PwC Ghana Banking Survey Report and the Ghana Statistical Service. Findings: Per the study analysis, it is established that in Model 1 (ROE), liquidity has no substantial influence on the profitability of the banks and when profitability is measured by ROE, it has an insignificant relationship with liquidity but in Model 2 where profitability is measured by ROA, it was revealed that there exists a significant relationship between profitability and liquidity. Financial leverage and profitability for both models 1 and 2 of the study show a significant relationship. It was also revealed that when profitability is measured by either ROE in model 1 or ROA in model 2, Liquidity has a greater moderating effect on the nexus between financial leverage and the profitability of banks. Unique Contribution to Theory, Policy and Practice: Therefore, the study concludes that there is a significant moderating effect of liquidity on the link between financial leverage and profitability of banks quoted on the Ghana Stock Exchange and therefore recommends that banks map up a good strategy in maintaining a good financial leverage level to help increase profits thereby increasing shareholders' value.